1979
DOI: 10.1002/art.1780221103
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the study of the role of sex hormones in autoimmunity

Abstract: Investigators from this laboratory have been studying sex hormones in normal and autoimmune mice for the past 10 years. We have found that immune responses to DNa are influenced by sex hormones. Androgens reduce and estrogens increase both spontaneous and immunization-induced antibodies to single-stranded DNA in NZB X NZW, NZB X C3H, NZB X CBA, NZB X DBA mice. Treatment of female NZB/W mice with testosterone or 5 alpha dihydrotestosterone retards the progress of autoimmunity. Castration is not necessary for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
4

Year Published

1981
1981
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(73 citation statements)
references
References 12 publications
3
66
0
4
Order By: Relevance
“…1 nM in females, it is suggested that testosterone may suppress immunoglobulin production also in vivo under normal conditions. On the other hand, oestrogen has been shown to augment humoral immune responses [1,7,11,12,33], and we also found that this hormone increased spontaneous immunoglobulin production by human PBMC in vitro at physiological concentrations (paper submitted). Collectively, these data suggest that human humoral immune responses may be controlled by the balance of these sex hormone levels.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…1 nM in females, it is suggested that testosterone may suppress immunoglobulin production also in vivo under normal conditions. On the other hand, oestrogen has been shown to augment humoral immune responses [1,7,11,12,33], and we also found that this hormone increased spontaneous immunoglobulin production by human PBMC in vitro at physiological concentrations (paper submitted). Collectively, these data suggest that human humoral immune responses may be controlled by the balance of these sex hormone levels.…”
Section: Discussionmentioning
confidence: 51%
“…Various studies have reported that testosterone suppresses humoral immune responses [1][2][3][4][5][6][7][8][9][10]. It is thus hypothesized that this hormone may have prophylactic and therapeutic effects on autoimmune diseases such as systemic lupus erythematosus (SLE) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Sex steroids affect the maturation of organ systems, including the immune system (47), and are thought to play a role in autoimmune disorders. Feminizing steroids are known to exacerbate SLE by stimulating the immune response (48,49). Estrogen has been associated with decreased levels of T cells and natural killer cells, and increased levels of B cells (47,50).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest in this context is further investigation of the reason for the strict male prevalence of the disease, seen after immunization of mice with homologous collagen, that is unusual in experimental as well as in human autoimmune disease (compare ref. 10).…”
Section: Discussionmentioning
confidence: 99%